ELISA Development for Serum Hemeoxygenase-1 and Its Application to Patients with Acute Respiratory Distress Syndrome. (18th April 2018) - Hara, Yu; Shinkai, Masaharu; Taguri, Masataka; Nagai, Kenjiro; Hashimoto, Satoru; Kaneko, Takeshi
Abstract : Background . Hemeoxygenase-1 (HO-1) is an essential enzyme in heme catabolism and has been proposed as a biomarker of lung disease prognosis. We modified a commercial HO-1 enzyme-linked immunosorbent assay (ELISA) kit to achieve higher sensitivity and evaluated if serum HO-1 could be a biomarker to predict the prognosis of acute respiratory distress syndrome (ARDS) patients. Methods . Serum samples were collected from 15 healthy volunteers to validate the modified ELISA. In the 22 patients with ARDS who were enrolled, serum HO-1 was measured upon diagnosis (D0) and at 7 days after diagnosis (D7). Results . The serum HO-1 concentration could be measured in all healthy volunteers. The intra- and interassay tests and the percentage recovery test were acceptable. Compared with normal control subjects, patients with ARDS had significantly higher D0 HO-1 concentrations (75.4 ng/mL versus 31.7 ng/mL, P < 0.001 ). The 28-day survival was significantly better in patients with low D0 HO-1 (<75.8 ng/mL) than in those with high D0 HO-1 (≥75.8 ng/mL) (mortality rate: 18% versus 73%, P = 0.016 ). Nonsurvivors had significantly higher D0 and D7 HO-1 concentrations than survivors (P < 0.05 ). Conclusion . Serum HO-1 may be a useful biomarker to predict the prognosis of patients with ARDS.